Use of Functionalized Resin for Matrix Separation and Trace Elements Determination in Petroleum Produced Formation Water by Inductively Coupled Plasma Mass Spectrometry. (2nd February 2012) - Santelli, Ricardo Erthal; Freire, Aline Soares; Oliveira, Eliane Padua; Lemos, Valfredo Azevedo; Novaes, Cléber Galvão; Bezerra, Marcos Almeida
Abstract : This work approaches the development of a procedure for separation and determination of five trace metals (Co, Cd, Pb, Ni, and Cu) from petroleum produced formation water. This procedure uses a styrene divinyl-benzene polymeric resin modified with 4-(5 ′ -bromo-2 ′ -tiazolilazo) orcinol, and the determination was performed by inductively coupled plasma mass spectrometry. A response surface methodology using a Doehlert matrix was used to optimize the solid-phase extraction of the studied elements. By using 50.0 mL of sample solution for separation/preconcentration, limits of quantification of 2.4, 14, 10, 11, and 350 ng L − 1 were obtained for Co, Cd, Pb, Ni, and Cu, respectively. The developed procedure was applied for determination of these trace elements in produced formation water from offshore platforms in the Brazilian Northeast.